2018
DOI: 10.1111/vec.12713
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new chest physiotherapy technique in dogs with airway fluid accumulation hospitalized in an intensive care unit

Abstract: PSE associated with AC are easily adaptable, well-tolerated techniques in dogs. The benefit of CP in dogs with airway fluid accumulation remains to be determined and it is hoped that future randomized controlled prospective studies may help answer this line of inquiry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 37 publications
2
11
1
Order By: Relevance
“…Our prospective randomized controlled study confirmed the effectiveness of CP, and more particularly of PSE and AC, on oxygenation As in a previous study, 18 we included in this prospective study many dogs with different signalment, ages varying from 1.7 to 7 years, body weight from 11.1 to 40 kg, and breeds from Pugs to Leonberg.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Our prospective randomized controlled study confirmed the effectiveness of CP, and more particularly of PSE and AC, on oxygenation As in a previous study, 18 we included in this prospective study many dogs with different signalment, ages varying from 1.7 to 7 years, body weight from 11.1 to 40 kg, and breeds from Pugs to Leonberg.…”
Section: Discussionsupporting
confidence: 77%
“…A previous study, using the same technique, reported a low discomfort rate, no adverse effects, and no deterioration of clinical parameters or desaturation during the sessions. 18 In our study, no adverse effects were noted during the sessions. No dogs had to be excluded from the CP group because of intolerance of CP.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…In this animal, the main interventions to reduce the bacterial load included suctioning the ETT with a sterile, flexible suction catheter every four hours and using a bacterial filter, which was replaced at regular intervals. Coupage was performed prior to suction to aid in the expulsion of airway secretions 33 . The ETT was replaced after 24 hours of use, although re‐intubation has been linked to increasing risk of VAP 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Coupage was performed prior to suction to aid in the expulsion of airway secretions. 33 The ETT was replaced after 24 hours of use, although re-intubation has been linked to increasing risk of VAP. 30 In this case there were visible secretions in the lumen of the removed ETT which proved irretrievable via suction.…”
Section: Discussionmentioning
confidence: 99%